An advanced switching moving boundary heat exchanger model with pressure drop. (May 2016) - Qiao, Hongtao; Laughman, Christopher R.; Aute, Vikrant; Radermacher, Reinhard
Highlights: An advanced switching moving boundary heat exchanger model is developed. Refrigerant pressure drop is calculated in a reasonably simple manner. Air flow propagation is taken into account in the model. Generalized switching schemes enable all possible model transition. Favorable agreement between simulation and experiment demonstrates model fidelity. Abstract: This paper presents an advanced heat exchanger model based on the moving boundary approach. Significant improvements have been made to overcome the deficiencies of the extant models. Air flow propagation is taken into account to provide a more accurate prediction of air side heat transfer for multi-row coils. Refrigerant pressure drop is calculated in a reasonably simple manner by solving the global momentum balance equation. The choice of state variables shows the benefits of mass conservation and good computational efficiency. Generalized switching schemes capable of supporting dynamic transition between all possible flow configurations are developed. Model integrity and stability are verified through simulations. The model is applied to explore the start-up transients of an R410a flash tank vapor injection system. Favorable agreement between simulation results and experimental data demonstrates that the proposed model can adequately capture the main transient heat transfer and fluid flow phenomena of the system.